2021
DOI: 10.1097/j.jcrs.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Infectious keratitis after corneal crosslinking: systematic review

Abstract: Infectious keratitis after corneal crosslinking is low. The use of topical steroids, bandage contact lenses, and/or a history of atopic or herpetic disease are associated with infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 85 publications
1
20
0
1
Order By: Relevance
“…Therefore, immediate postoperative steroid therapy could be considered. According to the review of Murchison et al, immediate postoperative steroid use has led to a higher incidence of infections 5 . This case shows that steroid therapy can also be started before epithelial closure without the development of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, immediate postoperative steroid therapy could be considered. According to the review of Murchison et al, immediate postoperative steroid use has led to a higher incidence of infections 5 . This case shows that steroid therapy can also be started before epithelial closure without the development of infections.…”
Section: Discussionmentioning
confidence: 99%
“…For keratitis post CXL, polymicrobial infection is much less common (8.1%) than single infection (91.9%) Murchison et al 40 Including the abovementioned 3 cases of fungal mixed microbial infection, a total of 5 polymicrobial keratitis cases have been reported. We found that bacteria were the most common pathogen in cases of polymicrobial infection, which can be found through culture or smear, as for the two cases we report herein.…”
Section: Discussionmentioning
confidence: 99%
“…Typical dendritic corneal ulcers can be detected by slit lamp microscopy; only 2 patients were diagnosed by Polymerase Chain Reaction Kymionis et al, 32 Yuksel et al 33 , and the remaining were easily diagnosed clinically due to typical signs Alqarni and Alharbi, 31 Sanjeeta et al 34 The infection was controlled with antiviral, anti-inflammatory, nutritional corneal tissue and other symptomatic supportive treatment, but residual slight corneal central scars remained. Overall, HSK infection is prone to recurrence, and repeated infections might lead to a gradual increase in corneal opacity Murchison et al 40 It is recommended that physicians be careful to avoid recurrence while treating postoperative HSK. Fungal infections started relatively late and had a long course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations